Achievements and lessons learnt in promoting Climate-Smart Agriculture implementation in Ghana through Science-Policy dialogue platforms - Sam, Kingsley Odum; Botchway, Vincent Ansah; Karbo, Naaminong; Essegbey, George Owusu; Nutsukpo, Delali Kofi; Segnon, Alcade C; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate change and variability is affecting all aspects of the development process. Agriculture and food systems are key vulnerable sectors to climate change impacts especially in the sub-Saharan Africa where Ghana is placed. In 2010, the Food and Agriculture Organization of the United Nations (FAO) introduced the concept of Climate-Smart Agriculture (CSA) as an integrated approach to managing landscapes that address the interlinked challenges of food security and accelerating climate change. CSA aims to simultaneously achieve three outcomes: increased productivity, enhanced resilience, and reduced emissions. Within this context, the role of institutions and policy and research cannot be overemphasized. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in West Africa has since 2012 supported the creation of national multi-stakeholder platforms on climate-smart agriculture in Burkina Faso, Ghana, Mali, Niger and Senegal. The platforms were established to use scientific evidence in order to create awareness on climate change impacts on agriculture and make recommendations on the mainstreaming of climate change and CSA into agricultural development plans. This info note aims to synthesize key milestones, achievements and lessons learnt over the last 8 years from the Ghana Science-Policy Dialogue Platform on climate-smart agriculture to inform policy influence and further research orientation on science-policy interaction.